Insecticide induced hormoligosis in Helicoverpa armigera on cotton (Gossypium hirsutum) - HARI, NIRMAL SINGH; MAHAL, MANJIT SINGH (The Indian Journal of Agricultural Sciences, 2011)
An experiment was conducted during rainy (kharif) season 2004 to study the sub-lethal effect of different insecticides on Helicoverpa armigera Hubner development, survival, growth and reproduction on Cotton (Gossypium hirsutum L.). Development, survival, growth and reproductive parameters of H. armigera (3rd instar larvae) treated with sub-lethal concentrations (LC30 and LC50) of different insecticides, viz spinosad, chlorpyriphos, endosulfan, acephate and cypermethrin were compared with the untreated control. Endosulfan LC30 treated larvae developed faster (14.9 days) than in control (17.9 days). Cypermethrin (LC30 and LC50), however, prolonged the development both in larval (21.8– 22.8 days) and cumulative immature (larva+pupa) (32.0–32.2 days) stages. The cumulative life-cycle (4th instar onwards) was shorter in endosulfan-exposed individuals than in control, whereas both treatments of chlorpyriphos and cypermethrin, spinosad LC30 and acephate LC50 prolonged it. Larval survival and overall adult emergence were adversely affected with sub-lethal use of different insecticides. Spinosad and cypermethrin exposure decreased pupal survival, while spinosad and endosulfan resulted in lighter pupae. The growth indices of immature stages in endosulfan LC30 was equivalent to that in control. The oviposition period and adult longevity was greater in chlorpyriphos (LC30 and LC50) and acephate LC50 treatments. The females laid more eggs in endosulfan LC30 (530.7/&) and acephate LC30 (529.8/&) treatments, while endosulfan LC50 (189.5/&) showed decreased fecundity. The egg hatchability was greater in cypermethrin LC50 (53.4%), whereas endosulfan adversely affected it. The overall consequences of the use of sub-lethal insecticides in relation to insecticide hormoligosis have been discussed.